2023
DOI: 10.1177/00238309231209311
|View full text |Cite
|
Sign up to set email alerts
|

English Vowel Discrimination and Perceptual Assimilation by Japanese Listeners

Yasuaki Shinohara,
Chao Han,
Arild Hestvik

Abstract: This study examined whether the discrimination accuracy of nonnative vowels could be predicted by how listeners assimilate nonnative phones into their L1. The results demonstrated that Japanese listeners discriminated between English /æ/ and /ʌ/ better than they did between /ɑ/ and /ʌ/, although they categorized all those stimuli as the Japanese /a/. Given that the acoustic distance between stimuli was controlled to be identical, this result was attributed not to the acoustic difference but to the category-goo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…For example, Escudero and Boersma (2004) demonstrated that L1 Spanish listeners' over-reliance on duration in perceiving the /i:/-/I/ in L2 Southern British English (SBE) can be accurately modeled by assuming that the SBE vowels are represented as /i, long/ and /i, short/ in the learners' phonological grammar, i.e., addition of a new length feature to an existing segmental category. Yazawa (2020) also proposed that Japanese listeners' perception of AmE /ae/ as a deviant, non-prototypical exemplar of Japanese /a/ or possibly /e/ (Strange et al, 1998;Shinohara et al, 2019Shinohara et al, , 2022 can be explained as a result of mismatch in height and frontness features, i.e., AmE /low, front/ (/ae/) is too front to be Japanese /low, central/ (/a/) and too low to be Japanese /mid, front/ (/e/). An important side note on these studies is that the learners' target variety (SBE or AmE) was explicitly specified, as is proposed within the L2LP model, which is essential for making accurate predictions and explanations regarding crosslinguistic perception patterns (cf.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…For example, Escudero and Boersma (2004) demonstrated that L1 Spanish listeners' over-reliance on duration in perceiving the /i:/-/I/ in L2 Southern British English (SBE) can be accurately modeled by assuming that the SBE vowels are represented as /i, long/ and /i, short/ in the learners' phonological grammar, i.e., addition of a new length feature to an existing segmental category. Yazawa (2020) also proposed that Japanese listeners' perception of AmE /ae/ as a deviant, non-prototypical exemplar of Japanese /a/ or possibly /e/ (Strange et al, 1998;Shinohara et al, 2019Shinohara et al, , 2022 can be explained as a result of mismatch in height and frontness features, i.e., AmE /low, front/ (/ae/) is too front to be Japanese /low, central/ (/a/) and too low to be Japanese /mid, front/ (/e/). An important side note on these studies is that the learners' target variety (SBE or AmE) was explicitly specified, as is proposed within the L2LP model, which is essential for making accurate predictions and explanations regarding crosslinguistic perception patterns (cf.…”
Section: Theoretical Implicationsmentioning
confidence: 99%